1993
DOI: 10.1161/01.hyp.22.2.257
|View full text |Cite
|
Sign up to set email alerts
|

De novo hypertension after liver transplantation.

Abstract: Hypertension develops in most patients after transplantation when immunosuppression is based on cyclosporine and prednisone. The pathogenesis appears to be multifactorial but involves rapidly rising vasoconstrictor tone in renal and systemic vascular beds. Much of this tone reflects abnormal vascular function, characterized by impaired prostacyclin and EDRF effects, in conjunction with increased vasoconstriction due to endothelin and possibly other factors. Effective management of the transplant recipient depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 94 publications
1
25
0
2
Order By: Relevance
“…[1][2][3][10][11][12]18 Earlier re- ports suggested a lower incidence of posttransplant hypertension with tacrolimus, although this may have reflected, in part, a shorter period of observation. 10,11,18 The mechanisms of early posttransplant hypertension appear to differ between cyclosporine and tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][10][11][12]18 Earlier re- ports suggested a lower incidence of posttransplant hypertension with tacrolimus, although this may have reflected, in part, a shorter period of observation. 10,11,18 The mechanisms of early posttransplant hypertension appear to differ between cyclosporine and tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Several reports have suggested that the incidence of hypertension in patients treated with tacrolimus (also called FK 506) is lower than that in patients treated with cyclosporine within the first year or two after kidney transplantation, [4][5][6] up to 3 years after heart transplantation, [7][8][9] and during the first year after liver transplantation. [10][11][12] We have observed, however, that the prevalence of hypertension in tacrolimus-treated patients increases in the second year after liver transplantation and may approach that observed in patients treated with cyclosporine.…”
mentioning
confidence: 99%
“…Concentrations of nitrite and nitrate were determined in serum samples stored frozen at Ϫ80°C. Before analysis, serum of these samples was deproteinized with 35% sulfosalicylic acid and the supernatants neutralized with NH 4 Cl buffer and NaOH. Concentrations of nitrite and nitrate were quantitated colorimetrically in supernatants after reaction with the Griess reagent.…”
mentioning
confidence: 99%
“…In our study, we found significantly higher levels of diastolic arterial pressure at rest and at peak exercise in transplanted subjects relative to that in controls,and no differences of systolic arterial pressure between groups 6,7 . The etiology of this complication seems to be multifactorial, having as a common final route the elevation of systemic vascular resistance [63][64][65][66][67] . The reason for the attenuated pressure response at peak exercise has not been clarified 18 .…”
Section: Work Ratementioning
confidence: 99%
“…In this situation cardiac output was similar to the normal. Another explanation for the excessive ventilatory response could be muscular respiratory dysfunction consequent to hypoperfusion and muscular fatigue 67,70 . Kavanagh et al 71 reported significant improvement in the respiratory response during exercise following physical training.…”
Section: Work Ratementioning
confidence: 99%